Impact ranking of microfinance institutions: an empirical study in India. (30th July 2019) - Singh, Prakash
The major source of growth for the Indian economy lies in its untapped resource of its substantial rural base. And one of the ways of reaching out to the rural base and making them part of the formal economy, thus bringing inclusive growth is by empowering them with basic banking products and services at an affordable cost. Microfinance (MFIs) is the provision of a broad range of financial services such as deposits, loans, payment services, money transfers, and insurance to poor and low-income households and, their micro enterprises. The MFIs do not have too many sources to raise funds from, which in a way limits their growth. Also, there is very little data available in public domain to investors who are seeking to analyse the financial performance. This paper aims to identify the key ratios that investors should look at when determining the value of an MFI. Operating self-sufficiency, portfolio at risk and efficiency of loan officer come out to be significant variables.